Desain UI/UX Aplikasi Unklab Mobile Student Dengan Metode Design Thinking - Biya, Antares Nathan Andrew; Kolibu, Mario Jonatan; Mambu, Joe Yuan; Tangka, George Morris William (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The Unklab Mobile Student application is an essential platform for Universitas Klabat students to access various academic services. However, the app currently suffers from shortcomings in features and design, leading to user dissatisfaction. This research employs a Design Thinking approach to redesign the application to be more responsive, intuitive, and visually appealing. Through a series of research methods, including interviews, questionnaires, observation, and data analysis, we gain a comprehensive understanding of user needs and existing problems. The analysis results are then used to formulate improved solutions, which include the development of efficient search features, a more intuitive layout, and enhanced design responsiveness. The resulting app prototype incorporates 17 features and is subjected to usability testing. The results demonstrate a significant increase in user satisfaction, with a high success rate of 60 in each tested task, indicating positive outcomes. This confirms the effectiveness of the Design Thinking approach in designing an application that better meets user needs.